Assessing Impacts of Changes in External Nutrient Loadings on a Temperate Chinese Drinking Water Reservoir - Chou, Qingchuan; Nielsen, Anders; Andersen, Tobias K.; Hu, Fenjuan; Chen, Weiyu; Zhang, Xiaolin; Cao, Te; Ni, Leyi; Jeppesen, Erik; Trolle, Dennis (Frontiers in Environmental Science, 2021)
The safety of drinking water is constantly being evaluated. In the last few decades, however, many drinking waters sources in the world, including in China, have undergone serious eutrophication and consequently water quality deterioration due to anthropogenic induced stressors such as elevated external nutrient inputs. In this study, we used the state-of-the-art complex, dynamic, mechanistic model GOTM-FABM-PCLake (a coupled one-dimensional hydrodynamic-lake ecosystem model) to quantitatively assess the impacts of external nutrient loading on the temperate Jihongtan reservoir in Shandong Province, China. Simulated values of all variables targeted in calibration (water temperature, dissolved oxygen, total nitrogen, total phosphorus, and chlorophyll a) agreed well with observations throughout the entire calibration and validation period and generally mimicked seasonal dynamics and inter-annual variations as found in the monitoring data. A series of scenarios, representing changed external nutrient loadings (both increasing and decreasing compared to the current nutrient load), were set up to quantify the effects on the reservoir water quality. Changes relative to the current external nutrient load had a significant effect on the simulated TN and TP concentrations in the reservoir. Our impact assessment indicate that TN will meet the Chinese water quality requirements of the water source (Class III) when the external nitrogen load is reduced by 70%, whereas TP will meet the requirements even if the external phosphorus load is increased by 100% relative to current loads. The model predicts progressively higher summer and autumn phytoplankton biomasses in the scenarios with increasing external phosphorus loading and potential toxic cyanobacteria will become more dominant at the expense of diatoms and other algae. Strict control of the external nutrient loading is therefore needed to maintain good drinking water quality in the reservoir.